2010
DOI: 10.1038/hr.2010.233
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of combination therapies, including the angiotensin receptor blocker olmesartan and either a calcium channel blocker or a thiazide diuretic, in elderly patients with hypertension

Abstract: The blood pressure goals set for the treatment of hypertensive patients have been lowered in recent guidelines. To reduce blood pressure levels sufficiently, combination therapies are often needed, but there is little evidence about which combination should be chosen. The present study was carried out to compare the effects of combination therapies, including the angiotensin receptor blocker olmesartan and either a calcium channel blocker (CCB) or a thiazide diuretic, in elderly patients with hypertension. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…According to the report of Shimosawa et al [22] combination therapy with losartan (50 mg)/hydrochlorothiazide (12.5 mg) and candesartan (8 mg)/amlodipine (5 mg), showed similar efficacy in blood pressure reduction. On the contrary, the study by Kato et al [23], whose participants were elderly patients with hypertension aged 65-85 years, showed a similar time course of the blood pressure until 6 months and the reductions in the SBP at 1 and 6 months were significantly greater in the CCB combination group than in the diuretic combination group, which was comparable to our study. Although the attainment speed of the BP goal in the two groups was different, the slow attainment in the ARB/HCTZ (12.5 mg) group might not be disadvantageous for elderly hypertensive patients as it reached the same level at 6 months.…”
Section: Discussionsupporting
confidence: 82%
“…According to the report of Shimosawa et al [22] combination therapy with losartan (50 mg)/hydrochlorothiazide (12.5 mg) and candesartan (8 mg)/amlodipine (5 mg), showed similar efficacy in blood pressure reduction. On the contrary, the study by Kato et al [23], whose participants were elderly patients with hypertension aged 65-85 years, showed a similar time course of the blood pressure until 6 months and the reductions in the SBP at 1 and 6 months were significantly greater in the CCB combination group than in the diuretic combination group, which was comparable to our study. Although the attainment speed of the BP goal in the two groups was different, the slow attainment in the ARB/HCTZ (12.5 mg) group might not be disadvantageous for elderly hypertensive patients as it reached the same level at 6 months.…”
Section: Discussionsupporting
confidence: 82%
“…The final 14 RCTs consisted of a total of 18,125 patients with hypertension. Among them, 8 RCTs recruited Asian subjects only, [ 13 15 , 18 , 20 , 21 , 23 , 24 ] while the other 6 RCTs were conducted in either mixed-race or unmentioned-race populations. Six RCTs compared the 2 combined treatments in 1001 patients with diabetes mellitus, [ 13 , 14 , 16 , 17 , 22 , 25 ] and 3 RCTs compared treatments in 1079 CKD patients.…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of quality and risk of bias are summarized in Table 1 . Five studies obtained Jadad scores lower than 3, [ 15 , 16 , 18 , 20 , 24 ] indicating low quality. The Cochrane Collaboration assessment suggested that 8 studies were at a high risk of bias [ 12 , 14 16 , 18 , 20 , 23 , 24 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recently published study [43] compared a combination of an ARB with a DHP-CCB versus an ARB with a diuretic. In this study, the authors showed greater reduction in SBP in patients receiving olmesartan and amlodipine compared with those receiving olmesartan and HCTZ.…”
Section: The Accomplish Trialmentioning
confidence: 98%